Difference Computation for Grammar-Compressed XML Data - Böttcher, Stefan; Hartel, Rita; Thiele, Sebastian (Proceedings of the Second Australasian Web Conference)

Keyword Search on DAG-Compressed XML Data - Böttcher, Stefan; Brandenburg, Marc; Hartel, Rita (Proceedings of the Second Australasian Web Conference)

Efficient XML Keyword Search Based on DAG-Compression - Böttcher, Stefan; Hartel, Rita; Rabe, Jonathan (Database and Expert Systems Applications - 25th International Conference, DEXA 2014)

Preference-based learning of ideal solutions in TOPSIS-like decision models - Agarwal, M.; Fallah Tehrani, A.; Hüllermeier, Eyke (Journal of Multi-Criteria Decision Analysis)

Extended graph-based models for enhanced similarity search in Cabase - Krotzky, T.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (IEEE/ACM Transactions of Computational Biology and Bioinformatics)

Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (International Journal of Approximate Reasoning)

Visualization of evolving fuzzy-rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (Evolving Systems)

Preference-based reinforcement learning: evolutionary direct policy search using a preference-based racing algorithm. - Busa-Fekete, Robert; Szörenyi, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Open challenges for data stream mining research - Krempl, G.; Zliobaite, I.; Brzezinski, D.; Hüllermeier, Eyke; Last, M.; Lemaire, V.; Noack, T.; Shaker, A.; Sievi, S.; Spiliopoulou, M.; Stefanowski, J. (SIGKDD Explorations)

Correlation-based embedding of pairwise score data - Strickert, M.; Bunte, K.; Schleif, F.M.; Hüllermeier, Eyke (Neurocomputing)

Survival analysis on data streams: Analyzing temporal events in dynamically changing environments - Shaker, Ammar; Hüllermeier, Eyke (International Journal of Applied Mathematics and Computer Science)

Reliable classification: Learning classifiers that distinguish aleatoric and epistemic uncertainty - Senge, Robin; Bösner, S.; Dembczynski, K.; Haasenritter, J.; Hirsch, O.; Donner-Banzhoff, N.; Hüllermeier, Eyke (Information Sciences)

The comprehensive diagnostic study is suggested as a design to model the diagnostic process - Donner-Banzhoff, N.; Haasenritter, J.; Hüllermeier, Eyke; Viniol, A.; Bösner, S.; Becker, A. (Journal of Clinical Epidemiology)

Fast Collisionless Pattern Formation by Anonymous, Position-Aware Robots - Lukovszki, Tamás; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

Continuous Aggregation in Dynamic Ad-Hoc Networks - Abshoff, Sebastian; Meyer auf der Heide, Friedhelm (Structural Information and Communication Complexity)

Time-causal material modeling in the simulation of guided waves in circular viscoelastic waveguides - Bause, Fabian; Schroder, Andreas; Rautenberg, Jens; Henning, Bernd; Gravenkamp, Hauke (2014 IEEE International Ultrasonics Symposium)

Unsicherheitsanalyse eines Vorwärtsmodells zur Simulation transienter Wellenausbreitung im Hohlzylinder - Bause, Fabian; Weber, Daniel; Rautenberg, Jens; Henning, Bernd

Model based sensitivity analysis of Leaky-Lamb wave propagation to the variation of viscous lubricant properties - Bause, Fabian; Brückner, Christoph; Miedl, Jens; Henning, Bernd (Beiträge der 17. ITG/GMA-Fachtagung)

Modellgestützte Analyse des Trocknungsverhaltens von Dispersionslacken aus Daten einer NIR-Multidetektoranordnung - Hoof, Christian; Appelhans, Silke; Henning, Bernd
Zur schnellen und berührungslosen Materialfeuchtebestimmung wird unter anderem die Infrarotreflexionsmessung ge-nutzt. In dieser Untersuchung wird das Trocknungsverhalten von Dispersionslack auf einem rauen Substrat mit einer Multidetektoranordnung untersucht. Durch diese Anordnung ist es möglich, gerichtete und diffuse Strahlungsanteile zu detektieren, wodurch zeitvariable Glanzeffekte an der Lackoberfläche miterfasst werden. Mit Hilfe eines Raytracing-Algorithmus wird die Trocknung eines Dispersionslackes simuliert und anhand von Messdaten mit einem FTIR-Spekt-rometer verifiziert.

Sensitivitätssteigerung im Rahmen eines inversen Ansatzes zur Materialparameterbestimmung für Piezokeramiken durch Elektrodenmodifikationen - Unverzagt, Carsten; Henning, Bernd
Simulationen mittels der Finiten Element Methode (FEM) sind heute ein fester Bestandteil im Entwicklungsprozess von Ultraschallsystemen. Durch die simulative Ermittlung der transienten Schwingungsvorgänge können Optimierungen bezüglich gewünschter Zielkriterien vorgenommen werden. Hierdurch lassen sich die aufwendige Prototypenfertigung reduzieren und günstige Entwurfspunkte schneller ermitteln.

On the computation of dispersion curves for axisymmetric elastic waveguides using the Scaled Boundary Finite Element Method - Gravenkamp, Hauke; Bause, Fabian; Chongmin, Song (Computers and Structures)

SAT-Based ATPG beyond Stuck-at Fault Testing - Hellebrand, Sybille; Wunderlich, Hans-Joachim (DeGruyter Journal on Information Technology (it))

Adaptive Bayesian Diagnosis of Intermittent Faults - Rodriguez Gomez, Laura; Cook, Alejandro; Indlekofer, Thomas; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Journal of Electronic Testing - Theory and Applications (JETTA))

Common Fate Graph Patterns in Monte Carlo Tree Search for Computer Go - Graf, Tobias; Platzner, Marco (2014 IEEE Conference on Computational Intelligence and Games)

Modeling and inverse identification of a high bandwidth ultrasonic measurement setup based on piezoelectric 1-3 composites - Bause, Fabian; Webersen, Manuel; Rautenberg, Jens; Henning, Bernd

Modellbasierte inverse Identifikation von Ultraschall-Transducern anhand der elektrischen Eingangsimpendanz - Bause, Fabian; Webersen, Manuel; Rautenberg, Jens; Henning, Bernd

PAC Rank Elicitation through Adaptive Sampling of Stochastic Pairwise Preferences - Busa-Fekete, Robert; Szörényi, B.; Hüllermeier, Eyke (Proceedings AAAI 2014, Quebec, Canada)

A Survey of Preference-Based Online Learning with Bandit Algorithms - Busa-Fekete, Robert; Hüllermeier, Eyke (Proceedings Int. Conf. on Algorithmic Learning Theory (ALT), Bled, Slovenia)

Mining Rank Data - Henzgen, Sascha; Hüllermeier, Eyke (Proceedings Discovery Science, Bled,Slovenia)

The Choquet kernel for monotone data - Fallah Tehrani, A.; Strickert, M.; Hüllermeier, Eyke (Proceedings ESANN , Bruges, Belgium)

Learning Solution Similarity in Preference-Based CBR - Abdel-Aziz, A.; Strickert, M.; Hüllermeier, Eyke (Proceedings Int. Conf. Case-Based Reasoning (ICCBR), Cork, Ireland)

Dyad Ranking Using A Bilinear Plackett-Luce Model - Schäfer, Dirk; Hüllermeier, Eyke (Proceedings Lernen-Wissensentdeckung-Adaptivität (LWA), Aachen, Germany)

Machine Learning and Knowledge Discovery in Databases-European Conf. ECML/PKDD, Nancy, France - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Proceedings, Parts I-III. Lecture Notes in Computer Science)

Preference Learning (Dagstuhl Seminar 14101) Dagstuhl Reports - Fürnkranz, J.; Hüllermeier, Eyke; Rudin, Cynthia; Slowinski, Roman; Sanner, Scott

Survival analysis on data streams: Analyzing temporal events in dynamically changing environments - Shaker, Ammar; Hüllermeier, Eyke (Applied Mathematics and Computer Science)

Ausgewählte Beiträge des GMA-Fachausschusses 5.14 - Hoffmann, F.; Hüllermeier, Eyke; Kroll, A. (Computational Intelligence Automatisierungstechnik)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Data Min. Knowledge Discovery)

Visualization of evolving fuzzy rule-based systems - Henzgen, Sascha; Strickert, M.; Hüllermeier, Eyke (Evolving Systems)

Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Rejoinder on "Learning from imprecise and fuzzy observations: Data disambiguation through generalized loss minimization - Hüllermeier, Eyke (Int. J. Approx. Reasoning)

Correlation-based embedding of pairwise score data - Strickert, M.; Bunte, K.; Schleif, F.- M.; Hüllermeier, Eyke (Neurocomputing)

Reliable classification: Learning classifiers that distinguish aleatoric and epistemic uncertainty - Senge, Robin; Bösner, S.; Dembczynski, K.; Haasenritter, J.; Hirsch, O.; Donner-Banzhoff, N.; Hüllermeier, Eyke (Information Sciences)

Protein Sub-Cellular Localization Prediction for Special compartments via Optimized Time Series Distances - Mernberger, M.; Moog, M.; Stork, S.; Zauner, S.; Maier, U.G.; Hüllermeier, Eyke (J. Bioinformatics and Computational Biology)

Guest editors`introduction:special issue of the ECML/PKDD 2014 journal track - Calders, T.; Esposito, F.; Hüllermeier, Eyke; Meo, R. (Machine Learning)

Preference-Based Reinforcement Learning: evolutionary direct policy search using a preference-based racing algorithm - Busa-Fekete, Robert; Szörényi, B.; Weng, P.; Cheng, W.; Hüllermeier, Eyke (Machine Learning)

Dependent binary relevance models for multi-label classification - Montanés, E.; Senge, Robin; Barranquero, J.; Quevedo, J.R.; Del Coz, J.J.; Hüllermeier, Eyke (Pattern Recognition)

Open challenges for data stream mining research - Krempl, G.; Zliobaite, I.; Brzezinski, D.; Hüllermeier, Eyke; Last, M.; Lemaire, V.; Noack, T.; Shaker, Ammar; Sievi, S.; Spiliopoulou, M.; Stefanowski, J. (SIGKDD Explorations)

Extended Graph-Based Models for Enhanced Similarity Search in Cavbase - Krotzky, T.; Fober, T.; Hüllermeier, Eyke; Klebe, G. (IEEE/ACM Trans. Comput. Biology Bioinform.)

Identification of Functionally Releated Enzymes by Learning to Rank Methods - Stock, M.; Fober, T.; Hüllermeier, Eyke; Glinca, S,; Klebe, G.; Pahikkala, T.; Airola, A.; De Baets, B.; Wageman, W. (IEEE/ACM Trans. Comput. Biology Bioinform.)

Power model design for ICT systems – A generic approach - Beister, Frederic; Dräxler, Martin; Aelken, Jörg; Karl, Holger (Computer Communications)

Design of an Electrical Interferometer at 120 GHz for Contactless Permittivity Characterization - Wessel, Jan; Schmalz, Klaus; Cahill, Brian; Scheytt, Christoph (Elektrotechnisches Kolloquium)

Architectural Low-Power Design Using Transaction-Based System Modeling and Simulation - Mischkalla, Fabian; Müller, Wolfgang (Embedded Computer Systems: Architectures, Modeling, and Simulation (SAMOS XIV))
Energy efficiency drives the development of more and more complex low-power designs. Based on dynamic power management techniques, multiple voltage islands as well as a huge amount of power states are specified that have to be tested carefully. In this context, low-power design should start at an early stage using state-of-the-art system-level modeling and simulation techniques. However, there is neither a programming language nor any modeling standard that reflects variable power together with its functional side effects in a well-suited abstract manner. To overcome this limitation, we present a modeling approach on top of SystemC TLM to capture low-power design characteristics at electronic system-level. We demonstrate the usability by means of an existing open-source low-power design. The experimental results show that appropriate TLM instrumentation cause only minimal simulation overhead, but offer sufficient details to identify common low-power design errors.

Switchable slow wave transmission line in 130 nm SiGe technology at 115 GHz for phase detection based biosensors - Wessel, Jan; Schmalz, Klaus; Scheytt, Christoph; Meliani, Chafik (Microwave Symposium (IMS), 2014 IEEE MTT-S International)
A 115 GHz slow wave transmission line intended for phase detection based integrated biosensors is presented. The structure was fabricated in a 130 nm SiGe process. It achieved the targeted overall phase shift of 1° at 115 GHz. Moreover, the phase can be adjusted by 16 switches using Heterojunction Bipolar (HBT) transistors leading to a phase resolution of 0.125°. The change in input and output matching over all configurations of the switches is not higher than 0.8 dB and the transmission S 21 varies with less than 0.7 dB. To the authors knowledge, it is the first switchable slow wave structure using microstrip transmission lines along with a bipolar switch circuitry. Moreover, the presented structure provides a very powerful solution for real-time digital read-outs in integrated biosensors, without need of additional signal processing steps.

A 7 GHz biosensor for permittivity change with enhanced sensitivity through phase compensation - Wessel, Jan; Schmalz, Klaus; Scheytt, Christoph; Meliani, Chafik; Cahill, Brian (European Microwave Conference (EuMC))
A calibration technique as well as measurement results for a 7 GHz Biosensor are presented. It is shown that the applied sensor structure can be calibrated by adjusting the phase of a sensing element's transmission S21. This is realized by slowing down the wave traveling a microstrip line serving as a reference in the differential sensor structure. The dielectric properties along with certain physical boundaries of an obstacle covering parts of the microstrip line evoke that effect. Measurements with an ethanol serious along with simulation results showed that sensitivity can be increased substantially with this calibration technique. A change of the real part of the sample's permittivity of 48 leads to a 18 MHz frequency shift.

Wireless 100 Gb/s: PHY layer Overview and Challenges in THz freqency band - Kraemer, Rolf; Wolf, Andreas; Scheytt, Christoph; Kallfass, Ingmar; KrishneGowda, Karthik (2014 IEEE 15th Annual IEEE Wireless and Microwave Technology Conference (WAMICON))
There is a continuous increase of bandwidth-demanding services such as ultra HDTV, 3D TV, etc. which will require data rates up to 100-400 Gb/s for short range wireless communication. This paper introduces a novel mixed-mode design where both analog and digital domain design is considered, which helps in the reduction of power consumption. Parallel Sequence Spread Spectrum (PSSS) is used for physical layer (PHY) baseband technology, which considerably alleviates both transmitter and receiver design.

Fast and Open Virtual Platforms for TriCore-based SoCs Using QEMU - Koppelmann, Bastian; Messidat, Bernd; Becker, Markus; Kuznik, Christoph; Müller, Wolfgang; Scheytt, Christoph (Design and Verification Conference (DVCON EUROPE))
In this paper, we present an efficient approach to virtual platform modeling for TriCore-based SoCs by combining fast and open software emulation with IEEE-1666 Standard SystemC simulation. For evaluation we consider Infineon's recently introduced AURIX processor family as a target platform, which utilizes multiple CPU cores operating in lockstep mode, memories, hierarchical buses, and a rich set of peripherals. For SoC prototyping, we integrate the fast and open instruction accurate QEMU software emulator with the TLMu library for SystemC co-verification. This article reports our most recent efforts of the implementation of the TriCore instruction set for QEMU. The experimental results demonstrate the functional correctness and performance of our TriCore implementation.

Verific-MM: Systematized Verification Metrics Generation with UCIS for Improved Automation on Verification Closure - Kuznik, Christoph; Müller, Wolfgang (Design, Automation and Test in Europe DATE, University Booth, Dresden)
Verific-MM is an approach to systematize and accelerate the coverage plan engineering as well as the verification environment’s (functional) metric code generation -- usually a time-consuming and error-prone task -- in particular by (i) improving automation via assisted model-based approaches, utilizing recent industry standards such as UCIS and (ii) a supporting methodology suitable for various target (functional coverage) languages (IEEE-1800 SystemVerilog, IEEE-1647 e, IEEE-1666 SystemC).

System-on-Chip Design für Funkfrequenzen oberhalb von 100 GHz-Herausforderungen und potenzielle Anwendungen - Scheytt, Christoph (Analog 2014,14. Fachtagung der Gesellschaft für Mikroelektronik, Mikrosystemtechnik und Feinwerktechnik des VDE und VDI)

A -Band Four-Element Butler Matrix in 0.13 µm SiGe BiCMOS Technology - Elkhouly, Mohamed; Mao, Yanfei; Meliani, Chafik; Scheytt, Christoph; Ellinger, Frank (IEEE JOURNAL OF SOLID-STATE CIRCUITS)

Safety Evaluation of Automotive Electronics Using Virtual Prototypes: State of the Art and Research Challenges - Oetjens, Jan-Hendrik; Becker, Markus; Kuznik, Christoph; Müller, Wolfgang; Bannow, Nico; Brinkmann, Oliver; Burger, Andreas; Chaari, Moomen; Chakraborty, Samarjit; Drechsler, R.; Ecker, Wolfgang; Grüttner, Kim; et al. (Design Automation Conference (DAC))
Intelligent automotive electronics significantly improved driving safety in the last decades. With the increasing complexity of automotive systems, dependability of the electronic components themselves and of their interaction must be assured to avoid any risk to driving safety due to unexpected failures caused by internal or external faults. Additionally, Virtual Prototypes (VPs) have been accepted in many areas of system development processes in the automotive industry as platforms for SW development, verification, and design space exploration. We believe that VPs will significantly contribute to the analysis of safety conditions for automotive electronics. This paper shows the advantages of such a methodology based on today's industrial needs, presents the current state of the art in this field, and outlines upcoming research challenges that need to be addressed to make this vision a reality.

Real-time capable methods to determine the magnet temperature of permanent magnet synchronous motors—A review - Wallscheid, Oliver; Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (IECON 2014-40th Annual Conference of the IEEE Industrial Electronics Society)

Determination of rotor temperature for an interior permanent magnet synchronous machine using a precise flux observer - Specht, Andreas; Wallscheid, Oliver; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014-ECCE ASIA))

Adaptable AC Input Phase Switching for Optimum Utilization of Various Grid Configurations supplying Power Electronic Converters and EV/HEV On Board Chargers - Schafmeister, Frank; Ide, Peter; Richter, Jörg (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

A Soft-Switching Interleaved DC-DC Converter with Integrated Magnetics for High Voltage Battery Charger - Li, Ronggyuan; Njiende, Hugues; Schafmeister, Frank; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Resistorless Precharging of Boost PFCs by Phase Angle Control of Thyristors - Schafmeister, Frank; Hufnagel, Michael; Ide, Peter (Proc. IEEE International Exhibition and Conference for Power Electronics, Intelligent Motion, Renewable Energy and Energy Management (PCIM))

Autonomously driven railway cabin convoys — Communication, control design and experimentation - Henke, Christian; Trächtler, Ansgar (2013 International Conference on Connected Vehicles and Expo (ICCVE))

Discrete-time design of adaptive current controller for interior permanent magnet synchronous motors (IPMSM) with high magnetic saturation - Peters, Wilhelm; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Monitoring critical temperatures in permanent magnet synchronous motors using low-order thermal models - Huber, Tobias; Peters, Wilhelm; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Real-time implementation of an online Model Predictive Control for IPMSM using parallel computing on FPGA - Leuer, Michael; Böcker, Joachim (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Efficiency-optimized Model Predictive Torque Control for IPMSM - Leuer, Michael; Ruting, Arne; Böcker, Joachim (2014 IEEE International Energy Conference (ENERGYCON))

FPGA-based dynamically reconfigurable control of induction motor drives - Buchholz, Oleg; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Power profile based selection and operation optimization of parallel-connected power converter combinations - Vogt, T.; Peters, A.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (2014 International Power Electronics Conference (IPEC-Hiroshima 2014 - ECCE ASIA))

Voltage sequence control based high-current rectifier system - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim; Duppe, Gregor; Averberg, Andreas; Wallmeier, Peter (2014 IEEE Energy Conversion Congress and Exposition (ECCE))

A completely modular power converter for high-power high-current DC applications - Solanki, Jitendra; Fröhleke, Norbert; Böcker, Joachim (IECON 2013 - 39th Annual Conference of the IEEE Industrial Electronics Society)

Ermittlung der Rotortemperatur einer Synchronmaschine mit eingebetteten Permanentmagneten für einen automobilen Traktionsantrieb mittels Beobachter basierend auf elektrischen Größen - Specht, A.

Model-Based Development of DC-DC Converters with Wide Operation Range and High Dynamics - Cao, Z.

Modeling Optimization and Control Design for LCC Resonant Converter Applied in Very Low Frequency High Voltage Generator - Hu, M.

Wirkungsgradoptimale Regelung eines elektrischen Fahrantriebes mit variabler Zwischenkreisspannung - Pohlenz, Daniel

Digital Control for Interleaved Boost Power Factor Correction (PFC) Rectifiers - Grote, T.

Modellprädiktive Regelung permanent erregter Synchronmotoren im Antriebsstrang von Automobilen - Leuer, M.

Evaluierung und Anwendung eines Emulators für elektrische Maschinen in der Entwicklung von Elektro- und Hybridfahrzeugen - Uebener, S.

Traktionsantrieb mit linearem geschalteten Reluktanzmotor für ein autonomes Bahnfahrzeug - Schneider, T.

Comparison of Hot Spot Investigations under Laboratory and Field Conditions at Photovoltaic Modules - Wendlandt, Stefan; Krause, Melanie; Berendes, Sarah; Hanusch, Matthias; Drobisch, Alexander; Berghold, Juliane; Schoppa, Michael; Grunow, Paul; Krauter, Stefan (Proceedings of the 29th European Photovoltaic Solar Energy Conference and Exhibition, Amsterdam (The Netherlands), September 22-16, 2014)

Variational formulation and structure-preserving discretization of nonlinear electric circuits - Ober-Blöbaum, Sina; Lindhorst, H. (21st International Symposium on Mathematical Theory of Networks and Systems)

On the role of quadrature rules and system dimensions in variational multirate integrators - Gail, T.; Leyendecker, S.; Ober-Blöbaum, Sina (3rd Joint Interntaional Conference on Multibody System Dynamics)

Case Study - Trächtler, Ansgar; Kleinjohann, Bernd; Heinzemann, Christian; Rasche, Christoph; Priesterjahn, Claudia; Steenken, Dominik; Wehrheim, Heike; Gausemeier, Jürgen; Flaßkamp, Kathrin; Kleinjohann, Lisa; Krüger, Martin; Iwanek, Peter; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Construction and analysis of higher order Galerkin variational integrators - Ober-Blöbaum, Sina; Saake, N. (Advances in Computational Mathematics)

Methods for the Design and Development - Anacker, H.; Dellnitz, M.; Flaßkamp, K.; Grocsbrink, S.; Hartmann, P.; Heinzemann, C.; Horenkamp, C.; Kleinjohann, B.; Korf, S.; Krüger, M.; Müller, W.; Ober-Blöbaum, Sina; et al. (Jürgen Gausemeier, Franz Josef Rammig, and Wilhelm Schäfer, editors, Design Methodology for Intelligent Technical Systems)

Dependability of Self-optimizing Mechatronic Systems - Dangelmeier, W.; Dellnitz, M.; Dorociak, R.; Flaßkamp, K.; Gausemeier, J.; Groesbrink, S.; Hartmann, P.; Heinzemann, C.; Hölscher, C.; Iwanek, P.; Keßler, J.H.; Kleinjohann, B.; et al. (Lecture Notes in Mechanical Engineering)

The paradigm of self-optimization - Dellnitz, M.; Dumitrescu, R.; Flaßkamp, K.; Gausemeier, J.; Hartmann, P.; Iwanek, P.; Korf, S.; Krüger, M.; Ober-Blöbaum, Sina; Porrmann, M.; Priesterjahn, C.; Stahl, K.; et al. (Jürgen Gausemeier, Franz Josef Rammig, and Wilhelm Schäfer, editors, Design Methodology for Intelligent Technical Systems)

Variational Lie group formulation of geometrically exact beam dynamics: Synchronous and asynchronous integration - Leitz, T.; Ober-Blöbaum, Sina; Leyendecker, S. (Zdravko Terze, Multibody Dynamics)

Equivariant spectral asymptotics forh-pseudodifferential operators - Weich, Tobias (Journal of Mathematical Physics)
Keywords: Mathematical Physics; Statistical and Nonlinear Physics

Die Rolle von Batteriespeichern in KMU-Microgrids - Vogt, T.; Böcker, Joachim; Kempen, S. (BWK – Das Energie-Fachmagazin – Springer VDI Verlag, Ausgabe 12-2014)

Design Considerations on Peak Power Clipping Thresholds in Microgrids - Vogt, T.; Fröhleke, N.; Böcker, Joachim; Kempen, S. (6th World Conference on Photovoltaic Energy Conversion (WCPEC))

Exponential ergodicity of killed Lévy processes in a finite interval - Kolb, Martin; Savov, Mladen (Electronic Communications in Probability)
Following Bertoin who considered the ergodicity and exponential decay of Lévy processes in a finite domain, we consider general Lévy processes and their ergodicity and exponential decay in a finite interval. More precisely, given Ta=inf{t>0:Xt∉. Under general conditions, e.g. absolute continuity of the transition semigroup of the unkilled Lévy process, we prove that the killed semigroup is a compact operator. Thus, we prove stronger results in view of the exponential ergodicity and estimates of the speed of convergence. Our results are presented in a Lévy processes setting but are well applicable for Markov processes in a finite interval under information about Lebesgue irreducibility of the killed semigroup and that the killed process is a double Feller process. For example, this scheme is applicable to a work of Pistorius.

The Brownian traveller on manifolds - Kolb, Martin; Krejčiřík, David (Journal of Spectral Theory)
We study the influence of the intrinsic curvature on the large time behaviour of the heat equation in a tubular neighbourhood of an unbounded geodesic in a two-dimensional Riemannian manifold. Since we consider killing boundary conditions, there is always an exponential-type decay for the heat semigroup. We show that this exponential-type decay is slower for positively curved manifolds comparing to the flat case. As the main result, we establish a sharp extra polynomial-type decay for the heat semigroup on negatively curved manifolds comparing to the flat case. The proof employs the existence of Hardy-type inequalities for the Dirichlet Laplacian in the tubular neighbourhoods on negatively curved manifolds and the method of self-similar variables and weighted Sobolev spaces for the heat equation.

mm-Wellen- und Electronic-Photonic System-on-Chip Design - Scheytt, Christoph (Fakultätskolloquium der Fakultät für Elektrotechnik und Informationstechnik)

Architectural Low-Power Design Using Transaction-Based System Simulation - Mischkalla, Fabian; Müller, Wolfgang (Embedded Computer Systems: Architectures, Modeling, and Simulation (SAMOS XIV))

Source code annotated memory leak detection for soft real time embedded systems with resource constraints - Joy, M. tech. Mabel Mary; Müller, Wolfgang; Rammig, Franz-Josef (12th IEEE International conference on Embedded Computing)